Is Social Media Impactful for University's Brand Image? - Wijaya, Bambang Sukma; M. Putri, Dianingtyas (SBM ITB, 2013)
This research aims to verify many opinions and previous studies that stated how powerful of social media in building the image of a brand, also applies for university's brand image enhancement. Using explanatory survey research, data were collected by giving out questionnaires to samples that were taken randomly from Facebook's friend list of a private university that located in South Jakarta. The results showed that the most powerful influence occurs on the role of 'community' towards the brand identity and the role of 'connectivity' towards the brand benefits. Another interesting finding of this research is, it turns out 'openness' and 'conversation' has no significant effect on all components that make up the brand image. Thus, it can be said that the positive image on the mind of consumer audience regarding the brand identity, personality, association, attitude or behavior and the benefit offered by a university's brand not necessarily be formed by the openness and willingness to dialogue or make conversations.Keywords: Social Media, Facebook, UB, Brand Image, University's Brand Image